An analysis of the rebound of the body in backward human running - Cavagna, G. A.; Legramandi, M. A.; La Torre, A. (The Journal of Experimental Biology, 2012)
Step frequency and energy expenditure are greater in backward running than in forward running. The differences in the motion of the centre of mass of the body associated with these findings are not known. These differences were measured here on nine trained subjects during backward and forward running steps on a force platform at 3-17 km h-1. In contrast to previous reports, we found that the maximal upward acceleration of the centre of mass and the aerial phase, averaged over the whole speed range, are greater in backward running than in forward running (15.7 versus 13.2 m s-2, P=1.9×10-6 and 0.098 versus 0.072 s, P=2.4×10-5, respectively). Opposite to forward running, the impulse on the ground is directed more vertically during the push at the end of stance than during the brake at the beginning of stance. The higher step frequency in backward running is explained by a greater mass-specific vertical stiffness of the bouncing system (499 versus 352 s-2, P=2.3×10-11) resulting in a shorter duration of the lower part of the vertical oscillation of the centre of mass when the force is greater than body weight, with a similar duration of the upper part when the force is lower than body weight. As in a catapult, muscle-tendon units are stretched more slowly during the brake at the beginning of stance and shorten more rapidly during the push at the end of stance. We suggest that the catapult-like mechanism of backward running, although requiring greater energy expenditure and not providing a smoother ride, may allow a safer stretch-shorten cycle of muscle-tendon units.